2020
DOI: 10.1097/sla.0000000000004455
|View full text |Cite
|
Sign up to set email alerts
|

Results of COVID-minimal Surgical Pathway During Surge-phase of COVID-19 Pandemic

Abstract: Objective: The outcomes of patients treated on the COVID-minimal pathway were evaluated during a period of surging COVID-19 hospital admissions, to determine the safety of continuing to perform urgent operations during the pandemic. Summary of Background Data: Crucial treatments were delayed for many patients during the COVID-19 pandemic, over concerns for hospital-acquired COVID-19 infections. To protect cancer patients whose survival depended on timely surgery, a “COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Other studies have demonstrated that the provision of COVID-19 “cold” sites reduces the risk of hospital-acquired COVID-19 infection and pulmonary complications. 15 , 28 , 44 46 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that the provision of COVID-19 “cold” sites reduces the risk of hospital-acquired COVID-19 infection and pulmonary complications. 15 , 28 , 44 46 …”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies on cancer care delays during the pandemic have focused on the rate and type of delays [1,2], clinical responses and potential consequences [21][22][23], and risk of Covid-19 infection or mortality among cancer survivors [24][25][26][27]. Studies on psychological distress during the pandemic indicate that both women and those with existing health conditions are at greater risk for distress, but have not indicated racial differences or disparities [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the very low risk of in-hospital death (one in 1000) among patients undergoing elective surgery who have not been infected with SARS-CoV-2 suggests that infection prevention and control procedures to create COVID-19-free ‘green’ surgical pathways have been highly effective during the pandemic. 20,21 Surgical patients with symptomatic SARS-CoV-2 infection were almost four times more likely to die compared to infected patients without respiratory symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 However, patients and clinicians should be reassured that the population incidence of SARS-CoV-2 among surgical patients is low and the overall risk of death from SARS-CoV-2 for a patient undergoing elective surgery in a ‘green’ pathway is less than one in 16500. 20 The predicted delays to surgical treatments as a result of the pandemic are substantial, with an estimated five million cases outstanding by March 2021. 4 Although the morbidity and mortality associated with cancelled or postponed surgery is unknown, it is clearly not desirable to have a large and rapidly expanding waiting list for treatments.…”
Section: Discussionmentioning
confidence: 99%